Inteligencia artificial y generación de contenido automatizado del medio digital “Positiva TV”, en Chimborazo - Maldonado Chauca, Natali Carolina (2025)
Positiva TV in Chimborazo. Qualitative and quantivative data were collected though a Through a mixed- methods approach to understand how automation has transformed communication dynamics. The findings reveal that while AI has optimized post frequency and improved engagement in some cases, challenges remain regarding authenticity perception and content depth. As a proposal, the study suggests integrating human oversight to balance technological efficiency with content quality, maximizing AI's potential in digital media